Lean and mean: network coding for commercial devices - Paramanathan, Achuthan; Pedersen, Morten V.; Lucani, Daniel E.; Fitzek, Frank H. P.; Katz, Marcos (IEEE wireless communications, 2013)
With its ability to reduce the number of transmissions in lossy networks as well as its potential to simplify the design and required signaling of communication protocols, network coding has emerged as an attractive solution to harness the power of wireless and cooperative networks in order to provide higher throughput and lower energy expenditure. This article shows that network coding's complexity is not an issue for current mobile devices even without hardware acceleration. We provide real-life measurements of energy savings gains of two design styles of network coding, namely, inter- and intra-session network coding using commercial platforms, including Open-Mesh routers and various mobile phones. We demonstrate that the energy per bit invested in coding/decoding operations can be several orders of magnitude smaller than that used for transmission/reception, while also maintaining processing speeds as high as several hundreds of Mb/s or even several Gb/s depending on the device and coding configuration used.